Comparison of Hip Extensor Muscles Activities According to Forward Trunk Lean Angles During Single-leg Deadlift - Saerin Lee; Duk-hyun An (Korean Research Society of Physical Therapy, 2023)
Background: Excessive hamstring (HS) activation due to the weakness of the gluteus maximus (GM) causes pain in the hip joint. A single-leg deadlift is a hip extensor exercise, especially GM, that includes functional movements in daily life and complex multi-joint training. In single-leg deadlift, the muscle activity depends on the forward trunk lean angle, and it's necessary to study which muscles are used dominantly depending on the angle. Objects: The purpose of this study was to compare the effect on the muscle activity of the GM and HS during single-leg deadlift according to different forward trunk lean angles and the ratio of the GM vs HS (GM/HS). Methods: Twenty-one healthy female participants were recruited. The muscles activities of the GM, HS and the GM/HS ratio were measured through electromyography during single-leg deadlift according to three condition of forward trunk lean angles (30°, 60°, and 90°). Results: The GM and HS activities significantly differed among three conditions (p < 0.05). GM/HS ratio was significantly higher at 30°and 60° of forward trunk lean compared to 90°. Moreover, the GM activity was significantly higher at 60°of forward trunk lean than at 30° (p < 0.05). Conclusion: The single-leg deadlift at 60°of forward trunk lean is a proper GM muscle strengthening exercise.